2015
DOI: 10.1186/s12959-015-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

Low dose compared to variable dose Warfarin and to Fondaparinux as prophylaxis for thromboembolism after elective hip or knee replacement surgery; a randomized, prospective study

Abstract: BackgroundDeep vein thrombosis (DVT) and pulmonary emboli (PE), known together as venous thromboembolic (VTE) disease remain major complications following elective hip and knee surgery. This study compares three chemoprophylactic regimens for VTE following elective primary unilateral hip or knee replacement, one of which was designed to minimize risk of post-operative bleeding.MethodsPatients were randomized and stratified for hip vs. knee to receive A: variable dose warfarin (first dose on the night preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
7
1
Order By: Relevance
“…This effect may be attributable in part to the mechanism of action, but also ease of administration and compliance in comparison to enoxaparin [9,39]. Data directly comparing factor Xa inhibitors with warfarin after TKA are limited, with a single randomized clinical trial finding no differences between the groups [7]. This contrasts with our study, in which factor Xa inhibitors showed better VTE prophylaxis when compared with warfarin.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This effect may be attributable in part to the mechanism of action, but also ease of administration and compliance in comparison to enoxaparin [9,39]. Data directly comparing factor Xa inhibitors with warfarin after TKA are limited, with a single randomized clinical trial finding no differences between the groups [7]. This contrasts with our study, in which factor Xa inhibitors showed better VTE prophylaxis when compared with warfarin.…”
Section: Discussioncontrasting
confidence: 87%
“…Despite this, we identified lower VTE incidence with comparable bleeding risk with factor Xa inhibitors in the patients who were most medically complex. Our findings regarding VTE prophylaxis do not have a direct correlate in the literature as other studies omit one or more of the two agents, but studies comparing multiple agents do help put our findings into context [3,7,21,22,24,38,40,41]. Aspirin has been found to have a low VTE rate, with no difference when compared with enoxaparin in a couple meta-analyses [3,40].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The literature search identified 1942 articles, of which 6 met the inclusion criteria and were specific to total joint replacement: 5 SRs and 1 RCT. A 2016 Cochrane review 112 synthesized a large number of contemporary RCTs (referred to as “trials” below); to this, we added 4 additional SRs 113 116 and 1 additional RCT 117 that have been published since the Cochrane literature search concluded.…”
Section: Resultsmentioning
confidence: 99%
“…Bern et al [56] randomized 355 patients in three groups A: variable dose warfarin (first dose on the night preceding surgery with subsequent target INR 2.0-2.5), B: 2.5 mg fondaparinux daily starting 6-18 h postoperatively, or C: fixed 1.0 mg dose warfarin daily starting 7 days preoperatively. All treatments continued until bilateral leg venous ultrasound day 28 ± 2 or earlier upon a VTE event.…”
Section: Comparison Of Different Methodsmentioning
confidence: 99%